Applying the plan‐do‐study‐act model to increase the use of kangaroo care. (22nd January 2013) - Stikes, Reetta; Barbier, Denise
Abstract : Aim : To increase the rate of participation in kangaroo care within a level III neonatal intensive care unit. Background : Preterm birth typically results in initial separation of mother and infant which may disrupt the bonding process. Nurses within the neonatal intensive care unit can introduce strategies that will assist parents in overcoming fears and developing relationships with their infants. Kangaroo care is a method of skin‐to‐skin holding that has been shown to enhance the mother–infant relationship while also improving infant outcomes. However, kangaroo care has been used inconsistently within neonatal intensive care unit settings. Methods : The Plan‐Do‐Study‐Act Model was used as a framework for this project. Plan‐Do‐Study‐Act Model uses four cyclical steps for continuous quality improvement. Based upon Plan‐Do‐Study‐Act Model, education was planned, surveys were developed and strategies implemented to overcome barriers. Results : Four months post‐implementation, the use of kangaroo care increased by 31%. Conclusions : Staff surveys demonstrated a decrease in the perceived barriers to kangaroo care as well as an increase in kangaroo care. Application of Plan‐Do‐Study‐Act Model was successful in meeting the goal of increasing the use of kangaroo care. Implications for Nursing Management: The use of the Plan‐Do‐Study‐Act Model framework encourages learning, reflection and validation throughout implementation. Plan‐Do‐Study‐Act Model is a strategy that can promote the effective use of innovative practices in nursing.